The Determinants of Eco-Fashion Purchase Intention and Willigness to Pay - Tribudhi, Debbie Aryani; Rhein, Verrel (Institute for Law and Economics Studies, 2025)
This study explores the factors that influence consumers' willingness to pay for eco-fashion, including Environmental Concerns, Social Influence, Altruism, Purchase Intention of Eco-Fashion (PIEF), Electronic Word-of-Mouth (eWOM), and Willingness to Pay (WTP) in Indonesia. The study focuses on the Indonesian fashion industry. The research aims to provide valuable insights for marketing managers on developing effective strategies to enhance the perceived value of eco-fashion, increase consumer awareness, and grasp consumer preferences. This research adds valuable insights to the academic understanding of the fashion industry in Indonesia by enhancing academic knowledge and practical appliaction